Issues in medical tourism - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Patient seeks medical treatment abroad for several reasons. It may be due to lack of expertise or lack of adequate equipment to handle the ailment in the country of abode. However, some may be due to social reasons or due to privileges that come with some social status and position. The study is justified by the need to high light some of the problems encountered by patients after treatment abroad.Materials and Methods:The case notes of three patients seen at the orthopaedic outpatient clinic were retrospectively reviewed. These patients had initially presented with different clinical problems. Data on their clinical history, examinations, investigations and treatment were extracted from their case note.Result:The first patient is a 53-year-old civil servant with clinical and radiological evidence of L4–L5 and L5–S1 disc degeneration with prolapse and neuropathy. He was cancelled for decompression and fusion. He opted to travel abroad for treatment. He represented few months later with the same complaint despite surgical treatment abroad. He had no physical evidence of what procedure was done. A second patient is a 68-year-old man with multilevel disc prolapsed and associated lumbar the canal stenosis. He was given the option of decompression with fusion. He opted to travel abroad, where he had L2–L5 laminectomy with pedicle screw stabilisation spanning three levels using four screws and two rods. His symptoms persisted despite procedure. He had evidence of the wrong choice of procedure. He is presently on conservative management as he does not want surgery. The third patient is a 50-year-old politician who presented with a painful gluteal swelling. She had transforaminal lumbar interbody fusion at L4–L5 with L2–S1 and laminectomy with L2–S1 pedicle screw stabilisation done abroad about 1 year before presentation. The indication being L4–L5 spondylolisthesis with L2–S1 multilevel disc prolapsed. She was found to have dislodged migrated rod. The rod was surgically extracted.Discussions and Conclusion:The First patient had the wrong/suboptimal procedure done to him. As such, he continued to have persistent pain. He cannot afford to go for appropriate procedure abroad. He is being planned for decompression and fusion. The second patient had suboptimal procedure. His pain continued. He could not afford to go for follow-up and re-evaluation. He also does not want any reoperation. He is now conservative management. The second patient had appropriate procedure done. However, she developed a technical complication which was not addressed appropriately. She had surgical extraction of the migrated rod and had done well.